From Protein Structure to Clinical Strategy: An In silico Investigation of Mitochondrial DNA Mutations in Type 2 Diabetes and Degenerative Disc Disease for Targeted Nutritional Interventions - Clinton, Tiffany Adelia (Stellenbosch : Stellenbosch University, 2026)
Thesis (MSc)--Stellenbosch University, 2026.